EFEKTIVITAS PENGGUNAAN BOOK CREATOR TERHADAP KEMAMPUAN BERCERITA - Gesti Aulia Putri, Syahrul Ismet; Serli Marlina, Yulsyofriend (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One way to improve children's storytelling skills is to use a book creator. Children can improve their storytelling skills expressively and their vocabulary increases through book creators. According to observations at Taman Kanak-kanak Bhayangkari 3 Padang, children have not been able to tell stories using the right expressions and have not used new vocabulary. So, it can be seen how effective book creators are in improving children's storytelling skills. This study uses a quantitative approach with the Quashi Experiment method. The population of this study were all children at Taman Kanak-kanak Bhayangkari 3 Padang, with samples of 12 children in grades B4 and B6. Data collection techniques used observation, tests, and documentation. Data analysis techniques used normality tests, homogeneity tests, and hypothesis tests. The data results were processed with the help of SPSS version 25 for Windows with a significance level of 5% (0.05). The results of the t-test for the experimental class using a digital-based book creator and the control class using picture story books were homogeneous. Then it was found that the sig value (2-tailed) was 0.035 <0.05. Thus, it can be concluded that Ha is accepted and H0 is rejected, indicating a significant difference in the learning outcomes between the experimental and control classes.